IMPLEMENTASI PEMBELAJARAN AKTIF DALAM MENINGKATKAN MOTIVASI SISWA PADA PEMBELAJARAN DI MA NURUL IMAN - Ageng Saepudin Kanda; Ririn Rustini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstraks Education is one of the key aspects in a country's development and individual development. A learning approach that encourages students to be actively involved in the learning process, not only as recipients of information, but also as active participants in their learning. Active learning can also overcome common problems in traditional learning, such as boredom, lack of student engagement, and lack of relevance in real-life contexts. This problem is the lack of effective learning carried out by teachers which makes students less motivated and also makes learning boring. Therefore, this research aims to apply active learning methods in the classroom to teachers and students in order to increase the level of student participation. The method used in this research is qualitative by explaining the application of the learning methods used to make them more effective. The results of this research are that after this active learning method is applied to learning, students become more active and are more able to express their opinions, apart from that, students' motivation in learning also increases because the learning method used is more enjoyable. Keywords: Learning, Active, Method, Motivation, Students